Creating Problemata with the Hippocratic corpus - Thomas, Oliver (Brill, 2015)
Discusses the various ways in which the Aristotelian Problemata engage with the Hippocratic Corpus, in particular the ways in which they convert Hippocratic material into their question-and-answer format.